Specialized neural dynamics for verbal and tonal memory: fMRI evidence in congenital amusia. Issue 3 (1st November 2018) - Albouy, Philippe; Peretz, Isabelle; Bermudez, Patrick; Zatorre, Robert J.; Tillmann, Barbara; Caclin, Anne
Abstract: Behavioral and neuropsychological studies have suggested that tonal and verbal short‐term memory are supported by specialized neural networks. To date however, neuroimaging investigations have failed to confirm this hypothesis. In this study, we investigated the hypothesis of distinct neural resources for tonal and verbal memory by comparing typical nonmusician listeners to individuals with congenital amusia, who exhibit pitch memory impairments with preserved verbal memory. During fMRI, amusics and matched controls performed delayed‐match‐to‐sample tasks with tones and words and perceptual control tasks with the same stimuli. For tonal maintenance, amusics showed decreased activity in the right auditory cortex, inferior frontal gyrus (IFG) and dorso‐lateral‐prefrontal cortex (DLPFC). Moreover, they exhibited reduced right‐lateralized functional connectivity between the auditory cortex and the IFG during tonal encoding and between the IFG and the DLPFC during tonal maintenance. In contrasts, amusics showed no difference compared with the controls for verbal memory, with activation in the left IFG and left fronto‐temporal connectivity. Critically, we observed a group‐by‐material interaction in right fronto‐temporal regions: while amusics recruited these regions less strongly for tonal memory than verbal memory, control participants showed the reversed pattern (tonal > verbal). By benefitting from the rare condition of amusia, our findings suggest specialized cortical systems for tonal and verbal short‐term memory in the human brain.